2021
DOI: 10.1109/access.2021.3063437
|View full text |Cite
|
Sign up to set email alerts
|

Neuromorphic Low-Power Inference on Memristive Crossbars With On-Chip Offset Calibration

Abstract: Monolithic integration of silicon with nano-sized Redox-based resistive Random-Access Memory (ReRAM) devices opened the door to the creation of dense synaptic connections for bio-inspired neuromorphic circuits. One drawback of OxRAM based neuromorphic systems is the relatively low ON resistance of OxRAM synapses (in the range of just a few kilo-ohms). This requires relatively large currents (many micro amperes per synapse), and therefore imposes strong driving capability demands on peripheral circuitry, limiti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
9
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 12 publications
(9 citation statements)
references
References 74 publications
(31 reference statements)
0
9
0
Order By: Relevance
“…One needs to consider, however, that the description of the different conduction states needs to be consistent with the idea of the reconfiguration of the oxygen defects. It should be noted that in state-of-the-art VCM cells, which show reproducible switching with high speed at comparably low voltages, the oxide layer is very thin and asymmetric electrode materials are used. …”
Section: Memristive Switching In Vcm Cellsmentioning
confidence: 99%
“…One needs to consider, however, that the description of the different conduction states needs to be consistent with the idea of the reconfiguration of the oxygen defects. It should be noted that in state-of-the-art VCM cells, which show reproducible switching with high speed at comparably low voltages, the oxide layer is very thin and asymmetric electrode materials are used. …”
Section: Memristive Switching In Vcm Cellsmentioning
confidence: 99%
“…This work has similar baseline design attributes with robotic smart homes based on stabilized feedback Episodic memory (SF-EM) [58], stewards robot smart homes [59], humanoid defense smart homes [60], Indoor autonomous robots [61], and Smart home activities IoT [62]. These similarities are highlighted below [63], [64], [65]:…”
Section: Summary Of Related Work (Automated Home)mentioning
confidence: 92%
“…Considering the memristive neuromorphic circuits used for computation acceleration, the work [42], [43], [44], showed that the synaptic circuit is required to represent process variable weights in binary form. The works equally highlighted that various synaptic circuits can be designed to utilize neuromorphic circuits.…”
Section: B Neuromorphic State Machine (Nsm)mentioning
confidence: 99%
“…In addition, the current of our devices with the smallest resistive area is more than 2 nA, which is big enough to read. In the pratical chip design, even the current of fA level can be collected by adding auxiliary circuits, such as operational amplifiers [41][42][43] .…”
Section: Device Design and Characterizationmentioning
confidence: 99%